Relative and absolute scarcity of nature: assessing the roles of economics and ecology for biodiversity conservation - Baumgärtner, Stefan; Becker, Christian; Faber, Malte; Manstetten, Reiner (Discussion paper series, 2004)
Our aim in this essay is to identify and analyze some of the difficulties with interdisciplinary integration of economic and ecological contributions to the study of biodiversity loss. We develop our analysis from a widely accepted definition of economics which is based on the concept of scarcity. Taking a closer look at this notion, we find that economics actually limits itself to a very particular aspect of scarcity, which we denote as relative scarcity. We describe in what respect the economic approach towards biodiversity is based on this notion, and also reflect on the specific understanding of the relation of humans and nature behind the economic approach. We then turn to absolute scarcity as another notion of scarcity, and show that this is not within the scope of economics, but has been a theme of ecology and ecological economics. We describe in which way ecological and ecologicaleconomic approaches towards biodiversity are based on the idea of absolute scarcity, and also reflect on the specific understanding of the human-nature relationship behind this notion of scarcity. Against this background, we discuss the roles of economics and ecology for nature conservation. We conclude that the interdisciplinary integration of ecology and economics requires a philosophical underpinning, and suggest a framework for further research.